Behavioral Problems in schools: A theoretical overview and the role of ICTs - Doulou, Aikaterini; Drigas, Athanasios (Technium Social Sciences Journal, 2022)
Behavior is a relative concept that is evaluated, analyzed, and interpreted based on subjective and social factors. Therefore, it is very likely that different people may characterize the same behavior as normal, desirable, problematic, or undesirable. According to international research, behavioral problems in childhood are the most common forms of dysfunction in interpersonal and social relationships and hinder severely a child’s ability to adapt to all levels of education. This paper investigates the behavioral problems that occur in the classroom and the role of ICT in controlling them. It aims to define what problematic behavior is, and what its causes are; to document its impact on the learning process and on the interpersonal relationships of students; and finally, to describe the role that the teacher assumes to prevent, to limit and intervene vigorously, in order to help the students solve their problems.